A review on development of adsorption cooling—Novel beds and advanced cycles. (April 2015) - Li, X.H.; Hou, X.H.; Zhang, X.; Yuan, Z.X.
Highlights: There are the plate-finned, the spiral plate, and the pin-fin bed for enhancement. To reduce the contact resistance the coated bed was proposed. Physical–chemical treatment was used to improve the conductivity of adsorbent. Heat recovery cycle is studied in depth and put into application. Mass recovery cycle showed better COP, thermal wave cycle not verified practically. Abstract: The performance of adsorption cooling cycle is highly affected by the heat and mass transfer in the bed, as well as by the cycling mode. Increasing the heat transfer area can effectively reduce the general transfer resistance of the bed. Popular methods to enlarge the transfer area include the plate-finned bed, the spiral plate bed, and the pin-fin bed. Incorporating the heat pipe into the adsorption bed causes the cycling time to decline and the COP to improve. To reduce the contact resistance between the adsorbent particulate and the bed wall, the coating method has been developed in which the slurry adsorption material is daubed onto the solid wall of the tube. Measurements of physical–chemical treatment can be used to improve the thermal conductivity of the adsorption material, but the over-compacted structure of the adsorbent will increase the mass transfer resistance. A few advanced cycling modes have been proposed to improve the performance of the adsorption cooling system. The heat recovery cycle has been studied in depth till today and put into practical application. Analysis of the mass recovery cycle showed that the COP can be increased as much as 100% in comparison to the simple cycle. As a novel cycling mode, the thermal wave cycle has presented the attractive result in the numerical study, while in the experiment it has not yet been verified practically. The surface cascade cycle consists of two stages of basic cycle. As the second cycle is operated at a lower driving temperature, the heat required is supplied by the desorbed vapor from the first stage and then the heat necessary from the outside heat source is decreased. The other advanced adsorption cycles include the multi-bed cycle, the multistage cycle, and the dual mode cycle etc.